SNOBERT: A Benchmark for clinical notes entity linking in the SNOMED CT clinical terminology - Kulyabin, Mikhail; Sokolov, Gleb; Galaida, Aleksandr; Maier, Andreas; Arias Vergara, Tomás (Proceedings of the 27th International Conference on Pattern Recognition 2024, 2024)
The extraction and analysis of insights from medical data, primarily stored in free-text formats by healthcare workers, presents significant challenges due to its unstructured nature. Medical coding, a crucial process in healthcare, remains minimally automated due to the complexity of medical ontologies and restricted access to medical texts for training Natural Language Processing models. In this paper, we proposed a method, "SNOBERT," of linking text spans in clinical notes to specific concepts in the SNOMED CT using BERT-based models. The method consists of two stages: candidate selection and candidate matching. The models were trained on one of the largest publicly available datasets of labelled clinical notes. SNOBERT outperforms other classical methods based on deep learning, as confirmed by the results of a challenge in which it was applied.<br
Keywords: NLP; SNOMED; BERT; Entity Linking; NER